LITERATURE REVIEW: POLA KEPEKAAN SALMONELLA TYPHI TERHADAP ANTIBIOTIK PADA PASIEN DEMAM TIFOID ANAK - Batosamma, Novatalia; Muthmainah, Noor; Rahmiati, Rahmiati; Pratiwi, Dewi Indah Noviana; Hayatie, Lisda (Homeostasis, 2023)
Typhoid fever is one of the major health problems in the world, especially in developing countries. The highest typhoid fever morbidity is found in children, especially school age children. Patients often self-medicate with antibiotics, the main antibiotic of choice for typhoid fever in Indonesia is chloramphenicol but in some places resistance to the chloramphenicol group has been reported. When writing, related literature is examined using search results from Google Scholar and PubMed - MEDLINE, two medical journal databases. articles from 2012 to 2019 that were published in English. This literature study contained a total of 8 papers. The article published in this literature review shows the presence of resistant isolates in the Salmonella thypi antibiotic susceptibility test in the main therapy given. In some cases, they have resistance to ceftriaxone, cefuroxime, amoxicillin, ampicillin, ciprofloxacin, augmentin, fluoroquinolones, azithromycin, and nalidixic acid. Some of the drugs mentioned as sensitive to S. Typhi are Cefixime, ceftriaxone, chloramphenicol, ofloxacin, cefepime, quinolones, and third generation cephalosporins.